Impact of Varying Concentrations of Myrtle Leaf Powder Aqueous Extract on Certain Chinese White Duck Carcass Characteristics - Alkenany , Moataz Hamzah; Al-Dhalimi , Hussain Mohammed; Ali , Sama Hussein; Al-Gharawi , Jassim Kassim; Raea , Naser Awad; Jahil, Firas Falih; Dinar, Ahmed Sachit; Jassiem , Rasha Mohmmed; Jrew , Mahdi Thamer; Hussein , Asmaa Dhyaa; Khudhair , Amal Abbas (American Journal of Biology and Natural Sciences, 2025)
A private Peking duck farm in Al Muthanna Governorate was occupied for this research study, from November 3rd, 2024, to December 2nd, 2025. For this study, we used sixty non-sexed, 1-day-old, 42-gram Peking ducklings. The ducklings were randomly distributed into four treatments, with three replicates each (5 ducklings in each replicate). The treatments were the following: a control treatment of no added materials - T1, and all treatments with an aqueous extract of powdered myrtle added in drinking water, T2 for 10 ml/liter, T3 for 20 ml/liter, and T4 for 30 ml/liter. The aqueous extract of myrtle leaves showed a significant improvement (P≤0.05) on all carcass traits, including dressing percentages with and without giblet (heart, liver, and gizzard) and the two main cuts (breast and thigh), and showed a significant difference (P≤0.05) in significantly reduced secondary cuts (neck, wings, and back for control) for the aqueous extract. The highest value in dressing percent and main cuts was achieved when the powdered myrtle was added to treated drinking water at 30 ml/liter, compared to all treatments in the experiment.